Manajemen Evaluasi Pendidikan terhadap Peningkatan Kualitas Pembelajaran Siswa di Lembaga Pendidikan Kepolisian di SPN Polda Maluku - Calvrin Saukoly; Tanwey Gerson Ratumanan; Paul Arjanto (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
Educational evaluation is a strategic element in ensuring the quality of learning in police education institutions. This study aims to comprehensively describe the implementation of educational evaluation management at SPN Polda Maluku. Employing a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis involving three key informant groups: managerial staff, instructors, and cadets. Findings reveal that evaluation is carried out systematically through planning, execution, and follow-up, engaging multiple actors and supported by digitalized tools and reporting systems. Evaluation encompasses not only academic performance but also integrity and operational readiness. This process demonstrates alignment between institutional demands and character development. The study highlights a context-sensitive and sustainable evaluative approach within police education. The implications emphasize the importance of establishing an independent evaluation unit, strengthening evaluative training for instructors, and updating adaptive technology-based systems in response to institutional dynamics.